Cytogenetic analysis of the cSOD microregion in Drosophila melanogaster. - Campbell, S.D.; Hilliker, A.J.; Phillips, J.P. (Genetics, 1986)
This report describes the genetic organization of a euchromatic region on the third chromosome of Drosophila melanogaster extending cytologically from 68A2 to C1, an interval comprising 10 or 11 polytene chromosome bands. The gene for cytoplasmic superoxide dismutase (cSOD) maps within this interval, as does low xanthine dehydrogenase (lxd).--Recessive lethal mutations were generated within the region by ethyl methanesulfonate mutagenesis and by hybrid dysgenesis. These lethals fall into 11 functional groups, which were partially ordered by complementation with deletions having breakpoints within the region. The distribution of dysgenesis-induced mutations in the region is highly nonrandom, the majority being within a single group. The mutability of this gene is comparable to that of singed (sn), a documented "hot-spot" for P-element insertion.--One of the EMS-induced lethals, l-108, fulfills biochemical criteria expected of a hypomorphic allele of cSOD. To our knowledge this is the first such allele recovered of this gene, and it should prove very useful in an analysis of the in vivo function of cytoplasmic SOD. Indeed, it has been demonstrated that cSOD is almost certainly a vital gene.